Kajian C-Organik Gambut Pedalaman pada Berbagai Tutupan Lahan - Alpandi Edison Pardede; Nina Yulianti; Akhmat Sajarwan; Sustiyah; Fengky Florante Adji (LPPM Universitas Palangka Raya, 2021)
The study aims to identify the C-organic content of inland peat in various land cover and soil layer depths. This study uses plot sampling methods with the creation of minipits on 4 (four) types of land cover. In each type of land cover, there are 3 (three) plot sampling, so the total plot sampling is 12 fields. Soil sampling is carried out at depths of 0-10 cm, 10-20 cm, 20-30 cm, 30-40 cm, and 40-50 cm. The research site is in the Special Purpose Forest Area (KHDTK) of Nusa Natural Laboratory and Peat Forest (LAHG) Sebangau. The study was conducted from June to August 2021. Soil samples are analyzed at the UPT Laboratory. LLG-Cimtrop and UPT. Integrated Laboratory, Palangka Raya University. The parameters observed are C-organic, Ash content, Moisture content, Water content, and Fiber content. The data of the study results are analyzed statistically with regression and correlation analysis. The results showed that the land cover that has the highest C-organic content is land revegetation (RePeat) at a depth of 40-50 cm with a C-organic value of 57.81% and the lowest C-organic content in natural forest cover at a depth of 30-40 cm with a C-organic value of 52.2%. The highest ash content is in natural forest cover at a depth of 30-40 cm with an ash content value of 3.18% and the lowest ash content in land cover revegetation (RePeat) at a depth of 40-50 cm with an ash level value of 0.08%. The highest water content is in the revegetation of land cover (RePeat) at a depth of 40-50 cm with a water content value of 318.97% and the lowest water content in the burned land cover at a depth of 0-10 cm with a water content value of 92.56%.